PERSPECTIVES OF ANTISENSE GENE THERAPY IN ORGAN TRANSPLANTATION - O. N. Reznik; A. E. Skvortsov; D. O. Kuzmin; A. P. Tutin; A. O. Reznik (Вестник трансплантологии и искусственных органов, 2013)
Global organ shortage is the crucial point of transplantation nowadays. Usage of expanded criteria donors represents reliable source of donor organs, making transplantation more accessible for patients with end stage organs failure. Ischemia-reperfusion injury followed by the activation of programmed cell death scenarios remains the main obstacle in utilization of marginal grafts. Programmed cell death often leads to life threatening complications in posttransplant period. Antisense gene therapy could provide a therapeutic tool, capable to improve quality of grafts and, consequently, transplantation outcomes.